Production, purification of the recombinant analog of Y-box-binding protein and its interaction with poly(ADP-ribose), RNA, single- and double-stranded DNAs - Alemasova, E.E.; Naumenko, K.N.; Pestryakov, P.E.; Lavrik, O.I. (Вiopolymers and Cell, 2017)
Aim. Production and purification of the recombinant histidine-tagged Y-box- binding protein and study of its interaction with DNA and poly(ADP-ribose). Methods. Ligation-independent cloning, PCR, Sanger sequencing, protein chromatography, polyacrylamide gel electrophoresis, and electrophoresis mobility shift assay. Results. cDNA coding for the YB-1 protein has a previously undocumented two single nucleotide polymorphisms. The expression construct for production of the his-tagged YB-1 protein was designed to simplify the purification procedure and an appropriate protocol for protein purification was developed. Using electrophoresis mobility shift assay, we have shown that poly(ADP-ribose) competes with a double- and single-stranded DNA and RNA for binding to purified recombinant his-tagged YB-1. Conclusions. In the present work we developed and optimized the procedure of the recombinant YB-1 protein production and purification from bacterial cells. We found that poly(ADP-ribose) at high concentration is able to recruit YB-1 protein from the YB-1-DNA and YB-1-RNA complexes, suggesting a possible YB-1 involvement in DNA repair. Мета. Отримання рекомбінантного гістидин-міченого Y-бокс-зв’язуючий білрк 1 і дослідження його взаємодії з ДНК, РНК та полі (АДФ-рибозою). Методи. Безлігазне клонування, ПЛР, секвенування по Сенгеру, хроматогра-фія, електрофорез в поліакриламідному гелі та метод затримки в гелі. Результати. кДНК YB-1 містить дві раніше недокументовані поодинокі нуклеотидні заміни. Сконструйовано вектор для експресії гистидин-міченого білка YB-1 і розроблена відповідна методика очищення білка. Методом затримки в гелі показано, що полі (АДФ-рибоза) конкурує з одно- і дволанцюговою ДНК, а також РНК, за зв›язування ре-комбінантного гістидин-міченого білка YB-1. Висновки. У цій роботі ми розробили та оптимізували процедуру отримання рекомбінантного білка YB-1 з бактеріальних клітин. Ми встановили, що полі (АДФ-рибоза) у високій концентрації здатна витісняти білок YB-1 з його комплексів з ДНК і РНК, що вказує на можливість участі YB-1 в репарації ДНК. Цель. Получение рекомбинантного гистидин-меченого Y-бокс-связывающего белка 1 и исследование его взаимо-действий с ДНК, РНК и поли(АДФ-рибозой). Методы. Безлигазное клонирование, ПЦР, секвенирование по Сэнге-ру, хроматография, электрофорез в полиакриламидном геле и метод задержки в геле. Результаты. кДНК YB-1 со-держит две ранее недокументированные одиночные нуклеотидные замены. Сконструирован вектор для экспрес-сии гистидин-меченого белка YB-1 и разработана соответствующая методика очистки белка. Методом задержки в геле показано, что поли(АДФ-рибоза) конкурирует с одно- и двухцепочечными ДНК, а также РНК, за связывание рекомбинантного гистидин-меченого белка YB-1. Выводы. В настоящей работе мы разработали и оптимизировали процедуру получения рекомбинантного белка YB-1 из бактериальных клеток. Мы установили, что поли(АДФ-рибоза) в высокой концентрации способна вытеснять белок YB-1 из его комплексов с ДНК и РНК, что указывает на возможность участия YB-1 в репарации ДНК.